Polarization Induced Changes in LSM Thin Film Electrode Composition Observed by In Operando Raman Spectroscopy and TOF-SIMS - McIntyre, Melissa D.; Traulsen, Marie Lund; Norrman, Kion; Sanna, Simone; Walker, Robert A (ECS transactions, 2015)
Polarization induced changes in LSM electrode composition were investigated by utilizing in operando Raman spectroscopy and post mortem TOF-SIMS depth profiling. Experiments were conducted on cells with 160 nm thick (La 0.85 Sr 0.15 ) 0.9 MnO 3 ±δ thin film electrodes in 10% O 2 at 700 °C under various electrical polarizations. Raman spectra recorded during polarization showed shifts in spectral intensities that were both reversible and dependent on the applied potential. Spectral changes were assigned to changes in the LSM electronic structure that resulted from changing oxide concentrations in the near-surface region. Ex situ TOF-SIMS depth profiles were recorded through the LSM electrodes and revealed distinct compositional changes throughout the electrodes. The electrode elements and impurities separated into well-defined layers that were more stratified for stronger applied polarizations. The mechanism(s) behind this layering remain unidentified and highlight important questions about mass transfer and ion migration in conducting metal oxide materials subject to electrical polarization.